Application of Integrated Nursing Intervention Model to Prevent Bullying Behaviour in Adolescent Children at SMA 6 Semarang - Sri Hartini Mardi Asih; Asti Nuraeni Nuraeni; Dayat Trihadi Trihadi (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2025)
ABSTRACT.Introduction: The Integrated Nursing Intervention Model was applied to adolescent children at SMA 6 Semarang to prevent bullying. Bullying behavior is a severe problem, and its impact on adolescents, families and schools. This study aimed to determine the effectiveness of implementing an integrated nursing intervention model to improve adolescents' developmental abilities and self-identity, improve self-concept, increase self-acceptance and ability to manage emotions. Interventions are carried out to build emotional closeness, such as building effective communication in managing emotions to reduce aggressive behavior. Method: This study used an operational research design with three stages: stage I problem identification, stage II model and module development, stage III trial of the integrated nursing intervention model to prevent bullying behavior using a quantitative quasi- experimental research study pre-postest with control group design, the research subjects were adolescents aged 13-15 years. The sample totaled 124 adolescents. The focus of this nursing intervention model is promotive and preventive bullying behavior.  Results: The results of applying the integrated nursing intervention model effectively improve the ability to develop adolescents' self-identity, self-concept, and self-acceptance after receiving integrated nursing interventions. In contrast, those who do not receive interventions do not significantly improve. The integrated nursing intervention model is a form of nursing service intervention in the community by adjusting adolescent growth and development stages.  Conclusions: This study provides input to the government to optimize the synergy between ministries in implementing the bullying behavior prevention intervention model as an alternative to promotive and preventive efforts for bullying problems adequately and appropriately